Secretion of von Willebrand Factor and Suppression of ADAMTS-13 Activity by Markedly High Concentration of Ferritin. (3rd February 2021) - Bashir, Dalia A.; Da, Qi; Pradhan, Subhashree; Sekhar, Nitin; Valladolid, Christian; Lam, Fong; Guffey, Danielle; Goldman, Jordana; Desai, Moreshwar S.; Cruz, Miguel A.; Allen, Carl; Nguyen, Trung C.; et al.
Hyperferritinemia is associated with poor outcomes in critically ill patients with sepsis, hemophagocytic lymphohistiocytosis (HLH), macrophage activation syndromes (MAS) and coronavirus disease 19 (COVID-19). Autopsies of hyperferritinemic patients that succumbed to either sepsis, HLH, MAS or COVID-19 have revealed disseminated microvascular thromboses with von Willebrand factor (VWF)-, platelets-, and/or fibrin-rich microthrombi. It is unknown whether high plasma ferritin concentration actively promotes microvascular thrombosis, or merely serves as a prognostic biomarker in these patients. Here, we show that secretion of VWF from human umbilical vein endothelial cells (HUVEC) is significantly enhanced by 100, 000 ng/ml of recombinant ferritin heavy chain protein (FHC). Ferritin fraction that was isolated by size exclusion chromatography from the plasma of critically ill HLH patients promoted VWF secretion from HUVEC, compared to similar fraction from non-critically ill control plasma. Furthermore, recombinant FHC moderately suppressed the activity of VWF cleaving metalloprotease ADAMTS-13. These observations suggest that a state of marked hyperferritinemia could promote thrombosis and organ injury by inducing endothelial VWF secretion and reducing the ADAMTS-13 activity.